An Evaluation of the Use and Effectiveness of Case Management in Clinical Nursing Education - Liang YM; Xie JY; Chen XH (Risk Management and Healthcare Policy, 2021)
Yu-Mei Liang,1 Jing-Yu Xie,1 Xiao-Hong Chen2 1Department of Nursing, Maoming People’s Hospital, Maoming, Guangdong Province, 525000, People’s Republic of China; 2Department of Neurosurgery, Maoming People’s Hospital, Maoming, Guangdong Province, 525000, People’s Republic of ChinaCorrespondence: Yu-Mei LiangDepartment of Nursing, Maoming People’s Hospital, No. 101 of Weimin Road, Maoming, Guangdong, 525000, People’s Republic of ChinaTel +86-0668-2922648Email liamgyumei@163.comBackground: This study aims to evaluate the use and effectiveness of case management in clinical nursing education.Methods: A sample of 181 nurses at the N3–N5 level were selected for clinical nursing education and divided into two groups using the random number method. The control group (n = 90) received traditional training, and the observation group (n = 91) received a case management model of training. The theoretical knowledge, nursing skills, training satisfaction, job stress, workplace mindfulness, career satisfaction, and job happiness of the two groups were compared. In addition, 50 patients were selected as subjects for each group, and their satisfaction with the nursing care that they received was also measured and compared.Results: Theoretical knowledge and nursing skills scored higher in the observation group than in the control group (p < 0.05), and overall training satisfaction was higher in the observation group than in the control group (p < 0.05). After training, job stress in the observation group was lower than in the control group (p < 0.05), while workplace mindfulness, career satisfaction, and job happiness were higher in the observation group than in the control group (p < 0.05). In terms of nursing quality, on all indicators, the observation group scored higher than the control group (p < 0.05), and the patients’ nursing satisfaction scores were higher in the observation group than in the control group (p < 0.05).Conclusion: Case management can improve the professionalism and overall skills of nurses at the N3–N5 levels. It is conducive to reducing job stress, enhancing workplace mindfulness, improving career satisfaction and job happiness, and improving the quality of nursing, thereby providing patients with better nursing care.Keywords: clinical nursing, nursing education, case management, nursing quality management, application evaluation